Od jezika k filozofiji in nazaj: Festschrift ob 75-letnici Dunje Jutronić - Borstner, Bojan; Onič, Tomaž; Zupan, Simon (2019)
From Language to Philosophy and Back:  A Festschrift for Dunja Jutronić on her 75th Birthday. The monograph is dedicated to Dunja Jutronić, retired Professor of English Linguistics at the University of Maribor, on the occasion of her 75th birthday. The volume comprises three sections corresponding to the research efforts of Professor Jutronić: English and American Studies, Philosophy and Translation Studies. Topics in the first section range from media discourse analysis, the language of advertising and appraisal-based language, on the one hand, to Canadian Literature, drama and science fiction, on the other. The philosophical chapters address the questions of language intuition, the origins of language, metaphor, the language of thought and the relation between language and the notion of identity. The third section comprises chapters on conference interpreting, translators’ professional identity, culture-specific terms in literary translation, media reporting about the Olympics and the recontextualization of “superfoods” in online advertising.
Keywords: Dunja Jutronić; Translation Studies; Philosophy; American Studies; English Studies